2022
DOI: 10.3390/ph15020245
|View full text |Cite
|
Sign up to set email alerts
|

Development of 18F-Labeled Bispyridyl Tetrazines for In Vivo Pretargeted PET Imaging

Abstract: Pretargeted PET imaging is an emerging and fast-developing method to monitor immuno-oncology strategies. Currently, tetrazine ligation is considered the most promising bioorthogonal reaction for pretargeting in vivo. Recently, we have developed a method to 18F-label ultrareactive tetrazines by copper-mediated fluorinations. However, bispyridyl tetrazines—one of the most promising structures for in vivo pretargeted applications—were inaccessible using this strategy. We believed that our successful efforts to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Suitable Tzs should be stable, highly reactive, clear rapidly from the blood stream, and easy to radiolabel. We have recently developed robust methods to radiolabel highly reactive Tzs with fluorine-18 as it is the most relevant radionuclide for clinical PET studies [ 48 , 49 , 50 , 51 ]. For brain pretargeted imaging, the Tz must also enter the brain.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Suitable Tzs should be stable, highly reactive, clear rapidly from the blood stream, and easy to radiolabel. We have recently developed robust methods to radiolabel highly reactive Tzs with fluorine-18 as it is the most relevant radionuclide for clinical PET studies [ 48 , 49 , 50 , 51 ]. For brain pretargeted imaging, the Tz must also enter the brain.…”
Section: Introductionsupporting
confidence: 84%
“…In the second step, the brain sections were incubated with 111 In-Tz for one hour. This timeframe was sufficient to achieve complete ligation of the available TCOs as 111 In-Tz is a bispyridyl tetrazine with an expected reaction timeframe within minutes [ 49 ]. Afterward, the excess 111 In-Tz was washed away and the sections were quantified and analyzed using the uptake values in the cortex and in cerebellum.…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41] They can be labeled with fluorine-18 40,41 and modified with a second handle, i.e., their physicochemical properties can also be manipulated. 41,42 Consequently, these scaffolds are ideal to develop a BBB penetrant Tz. Since previous studies have shown that addition of a single methyl group can dramatically affect the pharmacokinetics and distribution of CNS tracers, a homologation approach was employed stepwise increasing the length/bulk of the chosen side chain…”
Section: Tetrazine In Silico Parametersmentioning
confidence: 99%
“…39 We have recently developed methods to prepare highly reactive Tzs labeled with fluorine-18. [40][41][42][43] These methods were used to label all Tzs in this study. The respective development strategy is displayed in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…This method allowed for the use of non-nucleophilic bases for the elution of fluoride-18 from anion exchange cartridges (fluoride-18 is standardly trapped on these cartridges during its work-up), and reduced the basicity of the reaction [18]. Our group has advanced this methodology for the 18 F-labeling of highly reactive Tzs [17,21,[23][24][25]. In particular, we reported the first direct aromatic fluorination of Tzs from stannane precursors [23].…”
Section: Introductionmentioning
confidence: 99%